(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the economic, logistical, and geopolitical significance of the 21st Century Maritime Silk Road within the framework of the Belt and Road Initiative. The study examines the role of the Maritime Silk Road in the global trade system, the network of strategic ports, and China’s expanding international influence. Particular attention is paid to the geostrategic importance of ports such as Gwadar, Hambantota, and Piraeus, as well as the role of the China-Pakistan Economic Corridor (CPEC) in ensuring energy security. The article also discusses both the economic opportunities created for developing countries and the challenges associated with debt dependency, geopolitical competition, and strategic control.